A multi-level structure bio-carbon composite with polyaniline for high performance supercapacitors. Issue 16 (22nd January 2015) - Ma, Guofu; Wang, Haiping; Sun, Kanjun; Peng, Hui; Wu, Yajuan; Lei, Ziqiang
Abstract : The electrochemical performance of electrode materials can be enhanced by the synergistic effects of polyaniline and multi-level structured bio-carbon. Abstract : A novel activated carbon material with a multi-level structure is prepared by KOH-activation of chestnut shells at 800 °C (CAC8). The specific surface area and pore volume of the activated carbon obtained are as high as 1568.0 m 2 g −1 and 0.94 cm 3 g −1 . The electrochemical performance of the CAC8 is very promising; the specific capacitance is 207 F g −1 at a current density of 1 A g −1 in 1 M H2 SO4 electrolyte. A CAC8/PANI composite, which was synthesized through an interfacial polymerization method, presents a good electrochemical performance, including an excellent specific capacitance of 597 F g −1 and 80% retention of capacitance after 1000 cycles at a current density of 1 A g −1 in 1 M H2 SO4 electrolyte. The high electrochemical performance can be due to the use of the multi-level structured carbon, which improves the charge transfer performance of CAC8/PANI composite materials.